Estimating the prevalence of Parkinson's disease (PD) and proportions of patients with associated dementia and depression among the older adults based on secondary claims data. (14th January 2016) - Riedel, O.; Bitters, D.; Amann, U.; Garbe, E.; Langner, I.
Abstract : Objectives: While the epidemiology of Parkinson's disease (PD) has been extensively studied, data on the prevalence of PD among the older adults in Germany are scarce, based on small samples, and limited to primary data designs. This study estimated the PD prevalence among the older adults in Germany in 2006 using secondary data. Methods: We included 815, 573 health insurance members aged ≥65 years from all regions in Germany. PD was identified in case of at least one inpatient or outpatient diagnosis. An outpatient diagnosis had to be confirmed by either a subsequent diagnosis or an antiparkinsonian drug within 12 months. PD was also assumed if a first prescription was confirmed by a diagnosis within 12 months. Cases were checked for a diagnosis of dementia or depression. Results: The standardized prevalence of PD was 1680 (95% confidence interval (CI): 1644–1716) cases per 100, 000 persons. The prevalence increased with age and peaked in the age group of ≥90 years (4633 cases; 95% CI: 4227–5068) with higher rates in men (1729; 95% CI: 1684–1776) than in women (1644; 95% CI: 1593–1697). Dementia and depression occurred in 26.6% (95% CI: 25.8–27.5) and 32.6 (95% CI: 31.7–33.5) of PD cases, respectively. Conclusions: The age‐related increase of PD prevalence and the age‐specific prevalence estimates are in line with other European studies, stressing the public health relevance related to PD. In addition to the minimization of biases that might occur in primary data studies, further strengths of our findings are the large underlying sample size and the coverage of Germany.